2024
DOI: 10.3389/fonc.2024.1294253
|View full text |Cite
|
Sign up to set email alerts
|

Advanced lung cancer inflammation index predicts overall survival of hepatocellular carcinoma after hepatectomy

Yuan-Zhang Wen,
Gao-Min Liu,
Jia-Peng Liao
et al.

Abstract: AimLimited data are available regarding ALI’s clinical relevance and prognostic value in patients with hepatocellular carcinoma (HCC) after hepatectomy.Materials and methodsHCC patients who received hepatectomy at the Meizhou People’s Hospital from May 2011 to February 2022 were enrolled in the study cohort. The ALI was calculated as follows: ALI = BMI (kg/m2) × ALB (g/dL)/(absolute neutrophil count/absolute lymphocyte count). The primary outcome was overall survival (OS). The secondary outcome was cancer-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…This index can simultaneously re ect the nutritional and in ammatory status of patients [14]. he correlation between a lower ALI and poorer prognosis has been established in various cancers and in ammatory diseases [15][16][17][18][19][20][21]. Nonetheless, research on the clinical signi cance of the ALI in bronchiectasis patients remains limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This index can simultaneously re ect the nutritional and in ammatory status of patients [14]. he correlation between a lower ALI and poorer prognosis has been established in various cancers and in ammatory diseases [15][16][17][18][19][20][21]. Nonetheless, research on the clinical signi cance of the ALI in bronchiectasis patients remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…The Advanced Lung Cancer In ammation Index (ALI), which integrates BMI, the serum ALB concentration, and the neutrophil-to-lymphocyte ratio (NLR), was initially developed by Jafri et al to evaluate the prognosis of patients with metastatic non-small cell lung cancer (NSCLC) [14]. Subsequent studies have demonstrated that the ALI is effective in predicting the outcomes of various cancers, including hepatocellular carcinoma, esophageal squamous cell carcinoma, gastric cancer, colorectal cancer, and even benign conditions such as hypertension, acute coronary syndrome, and diabetes mellitus [15][16][17][18][19][20][21]. Additionally, the ALI has been utilized as a predictor of postoperative complications in colon cancer patients [22].…”
Section: Introductionmentioning
confidence: 99%